Embryonal origin of MTSCC of kidney may explain its morphological heterogeneity: diagnostic impact of genetic analysis - Banyai, Daniel; Yusenko, Maria; Bugert, Peter; Kovacs, Gyula (Anticancer research, 2017)
Background/Aim: Previous genetic and morphologic characterisation of mucinous tubular and spindle cell carcinoma (MTSCC) have yielded controversial results. The aim of this study was to explain the phenotypic heterogeneity of MTSCC diagnosed by genetic means. Materials and Methods: We analyzed 7 MTSCC by array CGH and microsatellite allelotyping and by histology for morphological variation. We worked-up two entire kidneys with MTSCC to find microscopic alterations. Results: We confirmed the diagnosis of MTSCC by detecting copy number changes at chromosomes 1, 4, 6, 8, 13, 14, 15, 18 and 22. We detected 13 small, microscopic precursor lesions in the two kidneys and found similar histological structures in precursor lesions and MTSCC. Conclusion: MTSCC develops from embryonal rest-like lesions of impaired differentiation which may explain its morphological variations. Until diagnosis of a “malignant” MTSCC” is not confirmed by genetic means, it should not be called carcinoma.
Published online March 16, 2017
Gesehen am 18.09.2018